Design of Web-Based Point of Sale Information System at Inti Peraga Mandiri - Faisal Amir; Riyanto; Fadhilah Oriyasmi; Fadli Fadilillah; Hafif Saputra (International ABEC, 2022)
Inti Peraga Mandiri is a business engaged in the sale of school teaching aids starting from kindergarten to high school levels. In carrying out its business, it is necessary to collect data, so that all types of transactions that occur can be monitored and checked by cashiers and business owners. The manual data collection process can be done, but the manual process has many shortcomings that can later cause losses for business owners. Based on these problems, this research focuses on building an automated Point of Sale (POS) system so that it can reduce misinformation and can help business owners in managing the flow of their business. POS is an application system applied to shops or supermarkets to handle the processing of data on purchase transactions, retail sales transactions, purchase return transactions, and transaction reporting which is generally important in making strategic decisions by self-service businesses, organizations, or small and medium-sized companies. The POS system is built on a web-based using the Waterfall model development method and system design using Unified Modeling Language (UML) diagrams. The results of this study get a POS system that has been developed and can carry out the transactions process, management of goods category, management of goods, manager of purchases, user management, and sales reports. Based on these results, it can be concluded that the point-of-sale system is running well and to the needs of business owners so that it can help develop their business.